Perhitungan Rab Rumah Sederhana Dengan Tinggi Plafon 3 Meter Vs 3,5 Meter - Gebi Gebi; Anggel Erpa Erong Pakiding (CV. SINAR HOWUHOWU, 2026)
Ceiling height in residential homes plays a vital role in regulating indoor air circulation and enhancing passive thermal comfort, particularly in tropical coastal environments such as Palopo City. While elevating ceiling height improves indoor environmental quality by increasing air volume and facilitating natural ventilation, it directly increases the volume of vertical architectural and structural elements, thereby impacting overall construction expenditure. This research investigates the financial implications of increasing ceiling height from 3.0 meters (Model A) to 3.5 meters (Model B) in a simple Type 36 residential unit. The study adopts a comparative quantitative descriptive approach utilizing basic mathematical geometric calculations to determine volume changes, combined with the standard activity unit pricing (AHSP) of Palopo City. The evaluation reveals that a 0.5-meter vertical extension produces an 18.6% increase in vertical surface material requirements, including practical column concrete volume (from 0.399 m³ to 0.466 m³), red brick masonry (from 112.50 m² to 133.50 m²), as well as plastering, acian, and wall painting areas (each increasing from 225.00 m² to 267.00 m²). Consequently, the total estimated construction budget (RAB) rises from Rp 97,650,000 for Model A to Rp 103,500,000 for Model B, creating an absolute cost difference of Rp 5,850,000 or a 5.99% overall budget increase. The cost increment is heavily driven by wall masonry, plastering, acian, and painting work, which account for Rp 5,540,000 (94.7%) of the total difference, while structural column extensions contribute Rp 310,000 (5.3%). In conclusion, allocating a 5.99% cost premium is a rational engineering investment for long-term thermal comfort in tropical regions, provided budget constraints permit.